2013
DOI: 10.1093/qjmed/hct141
|View full text |Cite
|
Sign up to set email alerts
|

The impact of number of drugs prescribed on the risk of potentially inappropriate medication among outpatient older adults with chronic diseases

Abstract: The number of prescribed medications can be an index of PIM risk in older patients with chronic diseases. Clinicians should suspect high PIM risk in older outpatients with ≥ 5 prescriptions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
77
2
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(94 citation statements)
references
References 33 publications
6
77
2
4
Order By: Relevance
“…In our analysis, inverse relationships were found between age and PIM use when the PIM-Taiwan and PRISCUS criteria were applied. In line with other studies [4], [18], [22], [27]–[29], we also demonstrated a relationship between higher disease burden, higher number of medications prescribed, and higher healthcare utilization with PIM use. Although these recipients had been regularly visited by home healthcare providers, these results suggested lack of continuity of care.…”
Section: Discussionsupporting
confidence: 92%
“…In our analysis, inverse relationships were found between age and PIM use when the PIM-Taiwan and PRISCUS criteria were applied. In line with other studies [4], [18], [22], [27]–[29], we also demonstrated a relationship between higher disease burden, higher number of medications prescribed, and higher healthcare utilization with PIM use. Although these recipients had been regularly visited by home healthcare providers, these results suggested lack of continuity of care.…”
Section: Discussionsupporting
confidence: 92%
“…In the multivariate analysis, it was found that increasing medication use (prescribed, non-prescribed and supplement use) was associated with PDDIs and PIMS after adjusting for age, sex, ethnicity and the number of comorbidities, as previously described [9, 72, 73]. In the present study, only drug interactions which were considered clinically significant and could potentially lead to serious consequences were assessed while PIMS identified the use of medications that had a high propensity to cause adverse events in the elderly population.…”
Section: Discussionmentioning
confidence: 57%
“…Other studies have demonstrated a clear relationship between an increasing number of medications and increase in unintended ADEs (6,8). This relationship is not linear; in fact, one Italian study demonstrated a fourfold increase in the risk of an ADE as the medication burden increased by only three individual medications, from five to eight (17).…”
Section: Discussionmentioning
confidence: 88%
“…We recognize that even one medication inappropriately prescribed can be burdensome to the patient. For the purposes of our analysis, we used the more common definition of five or more medications (8,16). Close to 94% of patients in our cohort experienced polypharmacy using this definition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation